Situasi Kesehatan Masyarakat Di Desa Kemang Indah Tahun 2021 - Suryani; Kursiah Warti Ningsih; Dwi Sapta Aryantisningsih; Roza Asnel; Winda Parlij; Rahmi Pramulia (STIKes Payung Negeri Pekanbaru, 2021)
In line with the health development strategy to realize a healthy nation by 2025, improving health status is one of the focuses of development in the health sector to create a healthy society, development in the health sector is directed at all levels of society to realize the Vision of Healthy Indonesia 2025. The role of health workers is obliged to facilitate in achievement of that goal. Therefore, an assessment of health problems was carried out which took place from January 25, 2021 to February 9, 2021, which was held in Kemang Indah Village. The purpose of this activity is to analyze or see the picture of public health in Kemang Indah Village in 2021. Based on 272 families that got several problems, namely 1% of families do not have latrines available, 47% of people do not do physical activity at least 30 minutes per day, 17% of people do not consume vegetables and fruit, 64% of people do not have a health check in 6 months, 35% of people still smoke at home, and 72% of people who do not manage stress.